Retroffiting of Telecommunication Tower via Tuned Viscous Mass Damper - Prajapati, Amrit; Xie, Liyu; Shrestha, Rameswor (Journal of Science and Engineering, 2024)
This paper proposes an innovative method to retrofit existing telecommunication towers by integrating Tuned Viscous Mass Dampers (TVMDs) into the tower. This method of retrofitting is designed to improve the seismic resilience of towers by controlling their lateral displacements and accelerations during ground motions. The TVMD includes a component that offers stiffness, connected with a ball screw device that can generate firm damping and inertial forces even with small deformations. In this system, TVMDs are connected in parallel with the existing V-shaped members of the tower. Such strategic TVMD configuration uses the advantage of the V-shaped braces in controlling the vertical displacement of the tower while focusing on the relative lateral displacement in both positive and negative directions. A single-mode tuning design method is presented here for the optimal design of the TVMDs, giving the ability to choose the tuning mode. Modal analysis is performed to determine the target tuning modes. After integrating the tower with TVMDs based on target tuning mode, time-history analyses are conducted to examine the seismic performance of the proposed system. The studies demonstrate the effective control of the TVMD integrated system when tuned to the third mode compared to the first mode.